1) Ek0 = Ek + Ep, Ek = Ep, Ek0 = 2Ep, mv0^2 / 2 = 2mgh, h = v0^2 / (4g),
h = 49^2 / 4*9.8 = 61,25 м
2) mv0^2 / 2 = mgh + mv^2 / 2, v = корень(v0^2 - 2gh) = корень(15^2 - 2*10*10) = 5м/с
3) mv0^2 / 2 = mgh + mv^2 / 2, v = v0/2, mv0^2 / 2 = mgh + mv0^2 / 8, 3mv0^2 / 8 = mgh, h = 3v0^2 / 8g, h = 3*10^2 / 8*10 = 3.75 м
4) A = Ek - Ek0 = mv^2 / 2 - mv0^2 / 2 = m/2(v^2 - v0^2), A = 0.5 кг/2(16^2 - 20^2) = -36 Дж
5) mv^2 / 2 - mgh = -FS, F = m/s(gh - v^2 / 2), F = 60/500(10*10 - 8^2 / 2) = 8.16 H
6) Ek0 = Ek + Ep, Ek = Ep, Ek0 = 2Ep, mv0^2 / 2 = 2mgh, h = v0^2 / (4g), h = 16^2 / 4*9.8 = 6,5 м
Объяснение:
1)
По условию:
ε = 2,5·W
W = ε / 2,5 = 0,4·ε
Запишем уравнение Эйнштейна для фотоэффекта:
ε = Авых + W
ε = Авых + 0,4·ε
0,6·ε = Aвых
ε = Aвых / 0,6 = 4,5 / 0,6 = 7,5 эВ